PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA BANK UMUM DI INDONESIA - Rizky Dwi Taruna; Setiawan Setiawan (Universitas Ma'soem, 2019)
The purpose of this research is to know the effect of Capital Adequacy Ratio (CAR), Operational Cost on Operating Revenue (OCOR) and Interest Risk Ratio (IRR) on Profit Growth partially or simultaneously at Bank BUKU III and BUKU IV in Indonesia period 2013-2017.The sample in this research are commercial banks in Indonesia which are included in the category of BUKU III and BUKU IV period 2013-2017 which contained 18 banks. The data used in this research is quantitative data obtained from the financial statement publications of bank. Data analysis method used is linear regression model.The results obtained from the research show partially CAR variable does not significantly influence but BOPO and IRR variables significantly influence the profit growth. Simultaneously variable CAR, BOPO and IRR have significant effect to profit growth. Simultaneously affect the profit growth by 17% and the remaining 83% influenced by other factor outside this research.